PENINGKATAN KUALITAS PEMBELAJARAN GURU MELALUI KEGIATAN KOMUNITAS BELAJAR - Sumarno (Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya Provinsi Kalimantan Barat, 2025)
This study aims to explore the role of learning communities at SMP Negeri 1 Kuala Mandor B in enhancing teachers' motivation to participate in professional development activities related to knowledge, skills, self-confidence, and the implementation of quality learning processes. This research employs a descriptive qualitative method. Data were collected through observation, interviews, and classroom supervision. Activities within the learning community include reviewing teaching modules, classroom teaching practice, and assessment. Teachers collaborate to share best practices in terms of experience, knowledge, and skills in order to determine more effective classroom teaching methods. Collaboration, innovation, and experience sharing among teachers play a vital role in the learning community to improve the quality of education in schools. Enhancing teachers' competencies significantly contributes to the realization of professional classroom management. Learning that applies varied models and strategies, as well as the implementation of differentiation, leads to effective classroom management. Effective learning is achieved through teachers’ competencies in selecting appropriate and varied teaching models or strategies, as well as optimizing student engagement in the learning process.